The qualitative assessment of median and transverse palatal sutures in various age groups - a CBCT analysis - Strzecki Adrian; Osiewacz Sandra; Jabłońska-Zrobek Joanna; Szczepańska Joanna; Pawłowska Elżbieta (Sciendo, 2018)
To detect age-related morphological changes occurring in the median and transverse palatal sutures that could affect the outcome of rapid maxillary expansion. Determined by Cone-Beam Computed Tomography (CBCT) scans.